Network interaction of institutional units: problems and defining points of growth for strategic effectiveness - Milekhina, O.V.; Adova, I.B. (St. Petersburg State Polytechnical University Journal. Economics, 2017)
Modern trends in the development of the global community (transition to knowledge economics, universal digitalization and technological development, rapid routinization of business processes, transformation of competitive preferences, etc.) necessitate the search for new forms of interaction of institutional units and their associations. The triple helix model and cluster theories are the conceptual basis for network interaction. The logical analysis of the state of the institutional environment and the strategies of the institutional units allowed to identify the problems of network interaction. It is proposed to transform the institutional environment so that it will allow to accomplish tasks of territory development and to monitor the strategical effectiveness of innovation programs. It is established that the emerging barriers to network interaction are to be eliminated gradually. The authors adapted the method of assessing the innovation development of the subjects of the Russian Federation for monitoring the transformation of the institutional environment. The basic indicator system was worked out in detail up to the level of individual institutional units. The authors designed a prototype of the expert system whose performance was demonstrated for the Novosibirsk, Tomsk, and Kemerovo regions and the Altai Krai. Further investigations are related to introducing new information pools into the expert system for assessing the institutional units.